A critical analysis of a randomized controlled trial evaluation in Mexico: Norm, mistake or exemplar?. (April 2014) - Faulkner, William N.
During the early stages of their flagship anti-poverty program, Progresa, Mexican officials contracted an evaluation team from the International Food Policy Research Institute (IFPRI). This article critically revisits the narrative of how this randomized controlled trial (RCT) was implemented, finding a number of significant omissions and ambiguities. By profiling the available information against the intellectual background of RCTs in international development evaluation and the political context of the project, the analysis extracts lessons about how results may be shaped, both during and after their production, by socio-political forces. These lessons derive two invitations: (1) for the proponents of RCTs in the field of international development evaluation to critically and reflexively consider the problematic framing of the methodology in this case study and what the implications might be for other similar projects; (2) for evaluators critical of how RCTs have been presented in the field to narrow their analyses to specific case studies, known econometric issues with familiar labels, and living institutions.